Elementary school students' motivational profiles across Finnish language, mathematics and science: Longitudinal trajectories, gender differences and STEM aspirations - Oppermann, Elisa; Vinni-Laakso, Janica; Juuti, Kalle; Loukomies, Anni; Salmela-Aro, Katariina (Contemporary educational psychology, 2021)
•Elementary students’ self-concept and intrinsic value profiles were examined.•Results revealed three profiles, which were moderately stable over one year.•Profile membership and profile transitions differed by gender.•A stable preference for math over one year was associated with STEM aspirations. The present study employed a person-oriented approach to (1) identify elementary school students’ self-concept and intrinsic value profiles across the subjects Finnish language, mathematics and science and to examine (2) the stability and change of these motivational profiles from 2nd to 3rd grade, (3) gender differences in profile membership as well as (4) the relation to students’ STEM (Science, Technology, Engineering and Mathematics) occupational aspirations. Based on data from 383 Finnish students (56.7% girls) three profiles were identified: High motivation across all three subjects, low motivation across all subjects, and a math-motivated profile with low motivation in the other two subjects. Latent transition analyses revealed moderate stability, particularly in the high motivation profile. Girls were less likely to be and to remain in the math-motivated profile, but they were more likely than boys to remain in the high motivation profile. The math-motivated profile transition pattern was associated with students’ STEM occupational aspirations.